Procedure for Perfecting Procurement in Cuban Fruit and Grain Networks (2016)
Introduction: this article addresses, from a historical perspective, the diffrent factors that have affcted the procurement process in two Cuban agricultural networks comprising two provinces of the country. For this reason, the main objective focused on proposing a procedure for perfecting it. Moreover, it assesses the diffilties that have hindered the implementation of the said networks based on the main policies governing the sector. Methodology: the historical, review and analysis methods as well as the group interview technique were applied to 93 attendees of the courses offred by the authors in the provinces of Sancti Spíritus and Santiago de Cuba, between December 2012 and January 2013. Results: this procedure for perfecting procurement in Cuban fruit and grain networks. Conclusions: the tools offred to the legal sector as part of the procedure cause the agricultural contract to further reflct the reality of stakeholders involved and their needs